1997
DOI: 10.1007/s001250050788
|View full text |Cite
|
Sign up to set email alerts
|

Muscular atrophy in diabetic neuropathy: a stereological magnetic resonance imaging study

Abstract: Motor dysfunction develops in advanced cases of diabetic polyneuropathy [1,2]. In the clinic it is most frequently detected by inability to walk on heels which indicates a preponderance for the dorsal flexors of the ankle. Recently weakness of both the ankle dorsal and plantar flexors and of the knee extensors and flexors was found in long-term insulin-dependent diabetic (IDDM) patients with peripheral neuropathy at isokinetic dynamometry [3]. Furthermore, the weakness at the ankle and knee was closely related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
186
4
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(211 citation statements)
references
References 23 publications
(28 reference statements)
13
186
4
3
Order By: Relevance
“…In the absence of appropriate active tension and decreased ROM, the contribution of passive components to the joint movement will increase [3]. It is well known that the strength of calf muscles [6] and ROM [9] are reduced in diabetic patients. This suggests that a greater proportion of the ankle moment during gait may come from passive structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of appropriate active tension and decreased ROM, the contribution of passive components to the joint movement will increase [3]. It is well known that the strength of calf muscles [6] and ROM [9] are reduced in diabetic patients. This suggests that a greater proportion of the ankle moment during gait may come from passive structures.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that under conditions of decreased active tension, such as ankle dorsal and plantar flexor weakness and atrophy resulting from diabetic neuropathy, passive tension may make a greater contribution to the total tension than that found in healthy individuals [6]. So in the absence of appropriate active tension, it is possible that a considerable portion of the ankle moment during gait may come from passive structures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on motor function in diabetic neuropathy have relied on simple clinical tests such as the ability to stand on heels (1) and neurophysiological examinations of motor nerves (2). In a series of experiments in long-term diabetic patients, we have observed that muscle weakness in the lowerleg muscles occurs to a substantial degree in chronic neuropathic patients, closely related to muscle atrophy, whereas nonneuropathic patients have normal muscle strength and striated muscle mass (3). In the more distally situated intrinsic foot muscles, Brash et al (4) observed atrophy in neuropathic diabetic patients using a specific magnetic resonance imaging (MRI) contrast sequence; however, the atrophy was not quantified.…”
mentioning
confidence: 99%
“…Muscle fascia, tendons, and blood vessels were excluded. At each image, the crosssectional area of all muscles was estimated by a single observer using a stereological point-counting method as described previously (3,5). The total volume of striated muscle (in cubic centimeters) was calculated by multiplying the distance between the sections by the total cross-sectional area, the first section being randomly placed within the first interslice 10-mm interval.…”
mentioning
confidence: 99%
“…Because of its multiplanar imaging capability and inherent superiority in tissue contrast, magnetic resonance imaging (MRI) is increasingly being used as a tool to assess structural pathology in the foot or lower leg of diabetic patients with peripheral neuropathy (5,(7)(8)(9)(10)(11). These assessments are considered important for improving our understanding of the relationship between structure and function in the foot and the pathogenesis of foot ulceration.…”
mentioning
confidence: 99%